Tungsten trioxide integrated all-fiber phase shifter - Bahtiar Affendy, Norhanie (2021)
All-fiber phase shifter is said to be one of the important components in optical communication and signal processing systems. Additionally, all-fiber phase shifter offers usage in electro-optic systems, fiber lasers, and sensors. The all fiber configuration is attractive due to advantages such as coupling simplicity and low insertion loss. Other than that, they also have a compact packaging and remote usage capability. Weak nonlinearity in conventional fiber imposes the use of extended length of fiber in order to trigger phase shifting. Another way to induce phase shifting includes introducing disruption into the fiber via mechanical deformation as well as acousto-optic effect. There is also effort in developing phase shifters using nonlinear optical phase modulation through cross-phase modulation and stimulated Brillouin scattering. Recently, researchers found another method of utilizing the thermal effect of nanomaterial attached to the microfiber. Previous works had introduced the usage of nanomaterials such as black phosphorus, graphene, and Au nanorods with all exhibiting promising performance. This work was focused on the development of optical fiber taper phase shifter deposited with tungsten trioxide (WO3), a nanomaterial that has recently been explored for various optical applications. The taper profile used across the experiment are; up and down taper of 5 mm, waist length of 10 mm and waist diameter of 12 μm. Tungsten trioxide (WO3) was synthesized via the mixing of WO3 solution with polydimethylsiloxane (PDMS). The concentration of WO3 was fixed using 5mg/mL for all the variation of spin coating time from 30 s to 150 s with the interval of 30 s and was then tested. The success of the nanomaterial deposition process was validated using UV Vis spectrometer, Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive X-ray Analysis (EDX), Atomic Force Microscope (AFM) and RAMAN Spectroscopy. For phase shifter characterization, pump power was varied from 0 to 220 mW with the interval of 20 mW. The thickness of coating was found to be a factor in the ability of WO3 to induce phase shifting effect. A blueshift with maximum phase shift of 2.52π and spectral shift efficiency of 0.011 π/mW were obtained for tungsten trioxide integrated all-fiber phase shifter with 120 s spin coating time. Phase shifter with the optimum spin coating time was then tested in a ring cavity laser. Phase shifting performance was observed at lasing threshold of 40 mW and maximum pump power of 100 mW. The wavelength coefficient obtained was 0.066 nm/mW and 0.057 nm/mW, respectively. This is because stronger gain from higher laser pump power has produced a stronger mode competition. From the results obtained, it is proven that WO3 can be used in phase shifter as it can induce thermo-optic effect. This work had offered advantage which cannot be offered by non-fiber phase shifter which it has a compact setup to suit current need in communication field.